Peran Pondok Pesantren Jabal Hikmah dalam Perubahan Sosial Masyarakat Desa Suwangi Timur Kecamatan Sakra Kabupaten Lombok Timur - Sukmawati Sukmawati (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
Pondok Pesantren is one of the Islamic educational institutions in Indonesia. Islamic boarding schools in historical records initially oriented themselves solely to religious education. But in its development, Islamic boarding schools do not remain silent, Islamic boarding schools continue to innovate so that they can adapt themselves according to the demands of the times. To maintain its existence in a global world with the demands of ever-changing times, Islamic boarding schools as Islamic educational institutions must be able to open themselves to the changes that occur, without having to abandon their main role as an Islamic educational institution that broadcasts religious teachings. The purpose of this research is To find out the role of the Jabal Hikmah Islamic Boarding School in social change from the aspects of religion, education and form social change from the aspect of religion and education in society. The type of research method used is a qualitative research method with the aim of obtaining data in the form of written or oral descriptions of the subject of observation, while the data collection procedures used by researchers are interviews, observation, and documentation. The role of the Jabal Hikmah Islamic Boarding School in social change from the religious aspect of the community is with a religious education system that is adapted to the needs of the community around the Islamic boarding school, so that it can provide output for students and alumni of Jabal Hikmah Islamic Boarding School graduates who can contribute and play a role in providing change from aspects of community religion through religious activities carried out in the community, leading the community in all forms of religious activities. Jabal Hikmah Islamic Boarding School by opening four formal educational institutions namely Raudatul Athfal, Islamic Junior High School, and Madrasah Aliyah Plus Skills provides and makes it easier for people to be able to get education.